THE STIMULATING AGENT OF SIBERIAN ANTHRAX AS A BIOLOGICAL WEAPON - Advienko, E.T.; Maliy, V.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The presentation of Siberian Anthrax as a biological weapon. Particularly started is the pathogenesis of the Inhalation form of the diseases, the modern way of therapy.